2013
DOI: 10.12691/ajmr-1-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Screening of Dye Decolorizing Bacteria

Abstract: The present study deals with the isolation, identification and screening of bacterial species capable to decolorize variety of dyes. Decolorization of dyes and growth of the bacterial species are investigated. The strain ETL-1942 decolorized all the selected dyes except Remazol Brilliant Blue R, Reactive Blue H5G, Remazol Turquoise Blue G and Fast Green. In our study, we identified three groups of dyes on the basis of the pattern of dye decolorization by strain ETL-1942. The results indicate that decolorizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…In the current study, the rate of decolorization is very fast reaching the maximal value of MB decolorization (51.7%) after the 1 st day of incubation. This result is matching with what obtained by Ong et al (2005) and Shah et al 2013 who found that the color of MB begins to disappear within a few minutes after incubation due to reduction by bacterial biomass reaching 28% after 24-h incubation. On the other hand, P putida decolourized 69% of MB after 7 days of incubation (Fulekar et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the rate of decolorization is very fast reaching the maximal value of MB decolorization (51.7%) after the 1 st day of incubation. This result is matching with what obtained by Ong et al (2005) and Shah et al 2013 who found that the color of MB begins to disappear within a few minutes after incubation due to reduction by bacterial biomass reaching 28% after 24-h incubation. On the other hand, P putida decolourized 69% of MB after 7 days of incubation (Fulekar et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Variation of UVvisible spectra of MB-containing supernatant of bacterial culture was checked at 0, 24 and 48 h spectrophotometrically where the maximum wavelength at 665 nm (Shah et al 2013). …”
Section: Mode Of Action Of Decolorizationmentioning
confidence: 99%
“…Strain isolation, screening for dye decolorization, identification of the newly isolated bacterium, and phylogenetic analysis Microbial strain having the ability to decolorize methyl orange was isolated from textile effluent water by the technique of enrichment Shah 2014). For enrichment of total heterotrophic population of methyl orange degrading isolates in the samples, 10 mL of the sample was aseptically added to 50 mL of enrichment medium, containing 100 mg/l methyl orange as a sole carbon source and were incubated at 37°C at 150 rpm.…”
Section: Growth Media Usedmentioning
confidence: 99%
“…Such structural alterations and degradation products of dyes (like aromatic amines) may result in the generation of new xenobiotic compounds that vary in their toxicity level (i.e. either become more or less toxic) in contrast to parent compounds (O'Neill et al, 2000;Vijaya and Sandhya, 2003;Franciscon et al, 2012;Shah et al, 2013).…”
Section: Need For Remediation Of Dyestuffs From Contaminated Substratesmentioning
confidence: 99%
“…Numerous researches have revealed the existence of a wide variety of microbial systems (bacterial and fungal species either as pure or mixed cultures) regarding efficient decolorization or degradation of colorants (Banat et al, 1996;Asgher et al, 2006;Singh and Arora, 2011;Singh et al, 2012) including Bacillus subtilis (Horitsu et al, 1977), Aeromonas hydrophila (Idaka and Ogawa, 1978), Bacillus cereus (Wuhrmann et al, 1980), Vibrio logei (Adedayo et al, 2004), Rhodopseudomonas palustris (Wang et al, 2008), Bacillus megaterium (Khan, 2011), Pseudomonas sp. (Shah et al, 2013), Sphingomonas sp. (Ali et al, 2014), Phanerochaete chrysosporium, Penicillium sp.…”
Section: Use Of Microbial Cells For Treatment Of Dyestuffsmentioning
confidence: 99%